Comparing methods suitable for monitoring marine mammals in low visibility conditions during seismic surveys. (January 2018) - Verfuss, Ursula K.; Gillespie, Douglas; Gordon, Jonathan; Marques, Tiago A.; Miller, Brianne; Plunkett, Rachael; Theriault, James A.; Tollit, Dominic J.; Zitterbart, Daniel P.; Hubert, Philippe; Thomas, Len
Abstract: Loud sound emitted during offshore industrial activities can impact marine mammals. Regulations typically prescribe marine mammal monitoring before and/or during these activities to implement mitigation measures that minimise potential acoustic impacts. Using seismic surveys under low visibility conditions as a case study, we review which monitoring methods are suitable and compare their relative strengths and weaknesses. Passive acoustic monitoring has been implemented as either a complementary or alternative method to visual monitoring in low visibility conditions. Other methods such as RADAR, active sonar and thermal infrared have also been tested, but are rarely recommended by regulatory bodies. The efficiency of the monitoring method(s) will depend on the animal behaviour and environmental conditions, however, using a combination of complementary systems generally improves the overall detection performance. We recommend that the performance of monitoring systems, over a range of conditions, is explored in a modelling framework for a variety of species. Highlights: Review of alternative marine mammal monitoring methods during seismic surveys. PAM, AAM, IR and RADAR are monitoring methods suited to low visibility conditions. No method's single performance suits all species and environmental conditions. The required detection performance may best be reached using complementary methods. Combined sensor performance can best be explored in a modelling framework.